Analisis Pengaruh UMKM, Investor Dan Tenaga Kerja Terhadap Peningkatan Ekonomi Di Kota Batam - Endy Widianto Fernando (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2021)
In analyzing GDP one of the most important things is determining development economic growth. If we want to achieve a goal, we need to make a good plan for stabilizing economic growth to improve the community peace, by increasing SME, Investor and Labor in Batam City. The data we got is secondary data and using panel data. The result of this study shows SME, Investor and Labor have been significantly affected by economic growth at Batam City. At Batam City, productivity has increased. That means if a lot of SME, Investor and Labor Increased, same as economic growth will also increase in Batam City.